Development of an improved RT-qPCR Assay for detection of Japanese encephalitis virus (JEV) RNA including a systematic review and comprehensive comparison with published methods. - Bharucha, T; Sengvilaipaseuth, O; Vongsouvath, M; Vongsouvath, M; Davong, V; Panyanouvong, P; Piorkowski, G; Garson, J; Newton, P; de Lamballerie, X; Dubot-Pérès, A (Public Library of Science, 2018)
Background Japanese encephalitis virus (JEV) is a major cause of encephalitis in Asia, and the commonest cause of mosquito-borne encephalitis worldwide. Detection of JEV RNA remains challenging due to the characteristic brief and low viraemia, with 0–25% of patients positive, and the mainstay of diagnosis remains detection of anti-JEV IgM antibody. Methods We performed a systematic review of published RT-PCR protocols, and evaluated them in silico and in vitro alongside new primers and probes designed using a multiple genome alignment of all JEV strains >9,000nt from GenBank, downloaded from the NCBI website (November 2016). The new assays included pan-genotype and genotype specific assays targeting genotypes 1 and 3. Results Ten RT-qPCR assays were compared, a pre-existing in-house assay, three published assays and six newly designed assays, using serial RNA dilutions. We selected three assays, one published and two novel assays, with the lowest limit of detection (LOD) for further optimisation and validation. One of the novel assays, detecting NS2A, showed the best results, with LOD approximately 4 copies/ reaction, and no cross-reaction on testing closely related viruses in the JEV serocomplex, West Nile Virus and St. Louis Virus. The optimised assays were validated in consecutive patients with central nervous system infections admitted to hospitals in Laos, testing paired CSF and serum samples. Conclusions We succeeded in developing a JEV specific RT-qPCR assay with at least 1 log10 improved sensitivity as compared to existing assays. Further evaluation is required, field-testing the assay in a larger group of patients.